Legal Protection for Copyright of Indonesian Cultural Heritage Claimed by other Countries from an International Law Perspective - Maulidina, Reva Alya Maulidina; Prastyanti, Rina Arum (IJBLE Scientific Publications Community Inc., 2025)
Legal protection of copyright on Indonesian cultural heritage claimed by other countries has become an important issue in the context of globalization and intercultural interactions between nations. From the perspective of international law, the protection of intangible cultural heritage is regulated through conventions such as the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage (2003). However, the implementation of this convention often encounters obstacles due to differences in interpretation and application at the national level. In Indonesia, although Law No. 28 of 2014 on Copyright and Law No. 5 of 2017 on the Advancement of Culture are in place, the protection of intangible cultural heritage still faces challenges in terms of documentation, international recognition, and law enforcement. Therefore, synergy between national regulations and international mechanisms is needed to strengthen copyright protection of Indonesia's cultural heritage against claims from other countries.